EFFECT OF WET MILLING TIME OF Nd-Fe-B FLAKES MATERIALS ON PARTICLE SIZE, MICROSTRUCTURE, AND MAGNETIC PROPERTIES - Sardjono, Prijo; Muljadi, Muljadi; Suprapedi, Suprapedi; Djauhari, Nenen Rusnaeni (Teknologi Indonesia, 2016)
The refining of Nd-Fe-B alloy flakes has been done by a wet mechanical milling method using a ball mill. This process is used to produce a fine powder for making permanent magnet materials. The variation of milling time was 16, 24, 48 and 72 hours and a milling medium was used a toluene (pa- Emerck)) to protect the particle from oxidation during the milling process. After milling processes, the samples' distribution particle size were measured by using Particle Size Analyzer (PSA). Microstructure analysis has been conducted by using X-ray diffractometer (XRD) and Scanning Electron Microscope (SEM/EDX) for samples after and before milling. Vibrating Sample Magnetometer (VSM) was used to measure magnetic properties. The characterization results show that the refining process with the wet ball mill obtained finest powder with average size about 1.49 μm for milling time of 48 hours. According to SEM/EDX and XRD analysis, it shows that the crystal structure of the sample before milling was different compared to the sample after milling. It is found new magnetic phase with formula Nd2 Fe14 B. The magnetic properties of sample after milling 48 hrs is higher than that of sample before milling.